Parent perspectives on digital play-based early literacy-learning in marginalized communities - Lauri Pynnönen; Kristiina Kumpulainen; Lasse Lipponen (Journal of Childhood, Education & Society, 2025)
This study examined parent perspectives on digital play-based learning for early literacy development in non-formal educational settings in Pakistan and Bangladesh, where access to quality education remains limited for marginalized communities. Drawing on neo-ecological theory as a guiding framework, we conducted a qualitative focus group study in which we analysed discussions with 40 parents whose children participated in a three-month digital play-based literacy intervention implemented through community learning centres and refugee camps. The parents reported significant improvements in their children's English language capabilities and digital literacies, often describing instances that reversed traditional knowledge hierarchies within families, with children teaching their parents English pronunciation and digital navigation. However, the parents simultaneously expressed concerns about traditional writing skill development and future educational transitions. The intervention affected parent–child engagement in education, with many parents reporting increased school visits and children showing a newfound enthusiasm for attending classes. Notable variations emerged between communities with different levels of prior educational access, with refugee parents in Bangladesh showing greater enthusiasm for digital interventions than those with previous exposure to conventional education. The study demonstrated how parents in marginalized communities carefully evaluated digital play through contextual lenses, and challenged simplistic narratives about technology adoption in resource-constrained environments. The parents’ perspectives highlight both the transformative potential of digital play for early literacy and the importance of contextually responsive approaches to implementing interventions.